A hybrid technique for damage detection on laminated plates - Lopes, Hernani (2006)
This work presents an experimental/numerical technique for delamination damage detection on thin laminated composite plates. The delamination is identified using a technique based on the curvature differences of the plate modes shapes measured before and after impact damage. The natural frequencies are extracted from Frequency Response Functions. A double pulse TV holography is used for no-contact and accurate measurement of the amplitude mode shapes. The curvature is obtained by applying an improved differentiation /smoothing technique to the experimental data. Finally, the curvatures of each mode are subtracted and the damage is located.